IMPLEMENTASI PERATURAN MENTERI NEGARA LINGKUNGAN HIDUP REPUBLIK INDONESIA NOMOR 13 TAHUN 2012 - Cahyo Sasmito (REFORMASI, 2017)
Abstract: Has conducted in March 2017 until May 2017 at Tlekung Village, Junrejo Sub-district, Batu City. Used descriptive qualitative research methodology. This research focused on: 1) Implementation of Public Participation for Successfuling independent Trash Bank, in: (a) planning, (b) implementation, (c) utilization of results, and (d) evaluation. 2) Supporting factors, on: (a) Opportunities to Participate, (b) Ability to Participate, and (c) Willingness to Participate for the Implementation of Community Participation in Realizing Independent Waste Bank. 3) Inhibiting factors for the Implementation of Community Participation in Realizing Independent Waste Bank, on: (a) low public response, and (b) low public awareness of environmental cleanliness. Data collection techniques used: observation, interview, and documentation. Used technique of determining the sample by purposive sampling. Research Instruments: Researchers themselves, using field notes, and interview guides. Data validity: triangulation, by checking from various ways, sources, and time. Keywords: Implementation, Participation, Concern.